"It Would 'Mean Little' Absent Governmental Recognition": Theorizing State Power and the New Jurisprudence of Dignity1. (October 2022) - Moore, Chelsea; Rodman, Emma
Dignity is increasingly central to the justificatory logic of US Supreme Court decisions. Yet the perils inherent in this jurisprudence of dignity, which we argue frames the right to dignity as a right to recognition, have been overlooked. Understanding dignity as synonymous with recognition clarifies its effects: dignity dethrones the autonomous, rights-bearing individual, instead figuring individuals as intersubjectively vulnerable and dependent upon institutional recognition. Dignity also casts state action as innocent, elides structural harms, and exacerbates injuries of marginalization. Applying our theoretical frame to Obergefell v. Hodges, we argue that the effects of the emerging jurisprudence of dignity are troubling.